EKSPRESI BAHASA INDONESIA TULIS BERDASARKAN GENDER PADA MEDIA FACEBOOK - Iin Fitriyani; Sudirman Wilian; Kamaludin Yusra (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to determine differences in the choice of topics of conversation between men and women on Facebook media. This study was qualitative in nature, examining the corpus of facebookers available on the internet. The process of data collection was done by referring to the record and documentation method. In the analysis process, data were classified and analyzed based on Tuncay's theory (2006) in determining the theme of masculinity and Cholik (2016) theory in determining the theme of femininity. The results showed that male users tended to upload themes to show their masculinity such as physical strength, altruism, women and sex, love and family, pleasure or fun, leadership, outdoor activities, as well as spirituality and morality, while female users tended to upload theme to reflect the feminine side, such as cooking, parenting, beauty, traveling, hobbies, and fashion.